In Memorium: Sammridhi Paudel - Chitrakar, Madan (SIRJANĀ – A Journal Of Arts and Art Education, 2018)
Sammridhi Paudel (June 16, 1989 – April 29, 2018) (Founder Member of Sirjana College of Fine Arts)